HIV/AIDS and the Agricultural Sector in Eastern and Southern Africa: Anticipating the Consequences - Jayne, Thomas S.; Villarreal, Marcela; Pingali, Prabhu; Hemrich, Gunter (International Food Policy Research Institute, 2006)
This chapter is intended to respond to the need to better understand the implications of the AIDS pandemic for the agricultural sectors in the hardest-hit countries of eastern and southern Africa. The six countries of the world with estimated HIV prevalence rates exceeding 20 percent1 are all in southern Africa: Botswana, Lesotho, Namibia, South Africa, Swaziland, and Zimbabwe (UN Census Bureau 2003). Five other countries, all in southern and eastern Africa (Cameroon, Central African Republic, Malawi, Zambia, and Mozambique), have HIV prevalence rates between 10 and 20 percent. For shorthand, we hereafter refer to these countries as the “hardest hit” countries.